2008
DOI: 10.1002/maco.200804132
|View full text |Cite
|
Sign up to set email alerts
|

Improving the oxidation resistance of γ‐titanium aluminides by halogen treatment

Abstract: A. Donchev * and M. Schü tzeIntermetallic alloys based on TiAl are candidates for several structural high temperature applications but their oxidation resistance is limited to temperatures below 800 8C. In this paper the results of high temperature oxidation and creep tests will be presented and discussed. The treatment with halogens improves the oxidation resistance of these alloys up to 1050 8C. A thin protective Al 2 O 3 -layer is formed after treatment with halogens instead of the mixed TiO 2 /Al 2 O 3 /Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…e addition of halogens has been investigated and concluded to support selective Al transport and improve adhesion between the formed Al 2 O 3 scale and the metal surface. For detailed information, the reader is referred to the following references [184][185][186][187][188][189].…”
Section: Influence Of Ternary Elements On Oxidation Resistancementioning
confidence: 99%
“…e addition of halogens has been investigated and concluded to support selective Al transport and improve adhesion between the formed Al 2 O 3 scale and the metal surface. For detailed information, the reader is referred to the following references [184][185][186][187][188][189].…”
Section: Influence Of Ternary Elements On Oxidation Resistancementioning
confidence: 99%
“…It is easily conceivable that the function of this rotor is no longer optimal. The left hand side of this figure shows the rotor with a special fluorine treatment applied before operation after the same type of exposure, and it becomes clear that the oxidation protection concept in this case is the only possibility to allow reliable operation of the turbo charger rotor without oxidation damage [37,38]. It should also be mentioned that titanium aluminide alloys have significant potential for use in jet engines as air foils, and the first engines with these materials are being manufactured in the United States by General Electric to be mounted to the wings of the new Boeing 787.…”
Section: Light Weight Construction In Transportmentioning
confidence: 99%
“…In other words, current thermal barrier coating systems are being used in order to increase lifetime and reliability of the system but not to increase efficiency. Increasing efficiency would, however, mean that the reliability of the ceramic topcoat with regard to spalling also has to be improved and guaranteed otherwise ceramic topcoat failure would expose the underlying metals to temperatures where [37,38] surface melting may commence. As recent research has revealed, the adherence of the ceramic topcoat is mainly dependent upon the thermally grown oxide scale on the intermetallic MCrAlY bond coat, which is applied to the nickel base substrate [40,41].…”
Section: Light Weight Construction In Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…A reliable and extensively studied technique to raise the oxidation resistance of these alloys up to 1050°C is a surface treatment with halogens, in particular fluorine, which provides a protective a-alumina layer [4][5][6]. Due to its simplicity and versatility, this technique has great potential for industrial applications, as was demonstrated for turbocharger rotors [7].…”
Section: Introductionmentioning
confidence: 97%